Directive diffusion film and preparation method thereof

By preparing specific scattering layer materials and wear-resistant layer materials in the diffusion film, the problems of poor light diffusion performance, wear resistance and corrosion resistance of the existing diffusion film are solved, and a more uniform light distribution and higher lighting efficiency are achieved.

CN119875184APending Publication Date: 2025-04-25TIAN CHENG (SHENZHEN) MICRO-ELECTRONIC MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510136919.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing diffusion films have poor light diffusion properties, wear resistance and corrosion resistance, making it difficult to effectively control the directionality of LED light sources, resulting in uneven coverage of the lighting area and visual discomfort.

Method used

Polyethylene terephthalate is used as the substrate, and the scattering layer material and wear-resistant layer material are prepared by preparing ethyl orthosilicate, tetrabutylamine bromide ethanol solution, decamethyl cyclopentasiloxane, tetramethyl tetravinyl cyclotetrasiloxane and octphenyl cyclotetrasiloxane, respectively, to form a directive diffusion film.

Benefits of technology

The light diffusion performance, corrosion resistance and wear resistance of the diffusion film are significantly improved, achieving a more uniform light distribution and higher lighting efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875184A_ABST
    Figure CN119875184A_ABST
Patent Text Reader

Abstract

The invention discloses a directional diffusion film and a preparation method thereof, and belongs to the technical field of diffusion film preparation. The directional diffusion film comprises a base material, a scattering layer is arranged on one side of the base material, and a wear-resistant layer is arranged on the other side of the base material; the base material layer takes polyethylene terephthalate as a raw material, and the scattering layer is prepared from tetraethoxysilane, a tetrabutylammonium bromide ethanol solution, decamethyl cyclopentasiloxane, tetramethyl tetravinyl cyclotetrasiloxane and octaphenyl cyclotetrasiloxane. The material of the wear-resistant layer is prepared from methyl methacrylate, butyl methacrylate, butenoic acid, hydroxyethyl methylacrylate, octamethylcyclotetrasiloxane and a polytetrafluoroethylene emulsion. The diffusion film obtained by the method has excellent light diffusion performance, wear resistance and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of diffusion film preparation, and in particular relates to a directional diffusion film and a preparation method thereof. Background Art

[0002] With the rapid rise of LED technology, this new solid-state light source has quickly occupied a core position in the lighting field with its high efficiency, long life, low consumption and environmental protection characteristics. However, an inherent characteristic of LED light sources - strong directivity, has become a major bottleneck restricting its widespread application. The light emitted by LEDs is often concentrated in a narrow angle range, which not only limits the coverage of the lighting area, but also easily causes glare problems, affects visual comfort, and may even cause potential damage to vision. Therefore, how to effectively control the directivity of LED light sources and achieve uniform diffusion of light has become a key issue that needs to be urgently solved in the field of lighting technology.

[0003] As an innovative optical element, the core function of directional diffusion film is to transform LED light source into a softer and more uniform surface light source. The key to this transformation lies in the design and preparation of the film material, which requires the film layer to have not only excellent light scattering ability to ensure that the light can be evenly distributed in the entire lighting area, but also maintain a high light transmittance to avoid loss of lighting efficiency.

[0004] Patent CN10690872B discloses a scratch-resistant diffusion film and a preparation method thereof, wherein the diffusion film comprises a substrate, a front coating is disposed on one side of the substrate, and a back coating is disposed on the other side; the front coating contains scattering particles; the surface of the front coating has a front coating microstructure, the front coating microstructure is hemispherical, and the diameter ranges from 30 to 70 μm; the back coating contains scattering particles; the surface of the back coating has a back coating microstructure, the back coating microstructure is hemispherical, and the diameter ranges from 5 to 30 μm. The diffusion film has good scratch resistance while ensuring optical performance. However, the light diffusion performance, wear resistance, and corrosion resistance of the diffusion film prepared by this method still have room for improvement. Summary of the invention

[0005] The object of the present invention is to provide a directional diffusion film and a preparation method thereof, so as to solve the technical problems of poor light diffusion performance, wear resistance and corrosion resistance of the diffusion film in the prior art.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The invention provides a directional diffusion film, which comprises a substrate, a scattering layer is arranged on one side of the substrate, and a wear-resistant layer is arranged on the other side; the substrate layer is made of polyethylene terephthalate as a raw material, the scattering layer material is prepared from tetraethyl orthosilicate, tetrabutylammonium bromide ethanol solution, decamethylcyclopentasiloxane, tetramethyltetravinylcyclotetrasiloxane and octaphenylcyclotetrasiloxane, and the wear-resistant layer material is prepared from methyl methacrylate, butyl methacrylate, crotonic acid, hydroxyethyl methacrylate, octamethylcyclotetrasiloxane and polytetrafluoroethylene emulsion.

[0007] Preferably, the method for preparing the scattering layer material comprises the following steps: Q1: Add anhydrous ethanol, distilled water and ammonia water into a container, stir and mix, then add tetraethyl orthosilicate to react, centrifuge and wash after the reaction to obtain silica particles; add anhydrous ethanol and ammonia water into a container, stir magnetically, add silica particles and tetrabutylammonium bromide ethanol solution, then add tetraethyl orthosilicate, react, centrifuge and purify to obtain inorganic particles; Q2: Add decamethylcyclopentasiloxane, tetramethyltetravinylcyclotetrasiloxane and octaphenylcyclotetrasiloxane into a container, heat and stir in an oil bath, then add tungsten oxide and benzyl alcohol into the container, stir and react, after the reaction is completed, add glacial acetic acid, dissolve, precipitate, and obtain an organic polymer; Q3: Add the obtained organic polymer and inorganic particles into a container, add dichloromethane and stir, then add photosensitive adhesive, stir evenly, and let stand to obtain a scattering layer material.

[0008] In the above process, firstly, silicon dioxide particles are prepared and used as seed particles, then tetrabutylammonium bromide is used as a ligand and tetraethyl orthosilicate is used as a silicon source to prepare inorganic particles, and then tungsten oxide is used as a catalyst, benzyl alcohol is used as an initiator, decamethylcyclopentasiloxane, tetramethyltetravinylcyclotetrasiloxane and octaphenylcyclotetrasiloxane are used as monomers to undergo a polymerization reaction to obtain an organic polymer, and then the organic polymer, the inorganic particles and a photosensitive adhesive are mixed to prepare a scattering layer material.

[0009] Preferably, in Q1, the dosage ratio of anhydrous ethanol, distilled water, ammonia water and tetraethyl orthosilicate is (80-120) mL: (2-3) mL: (6-10) mL: (2-3) mL, the stirring mixing temperature is 30-35°C, the stirring speed is 300-400 rpm, the time is 10-15 min, the reaction time is 6-8 h, the centrifugal speed is 10000-12000 rpm, the time is 10-12 min, and the distilled water and ethanol are used. Washing is performed; the dosage ratio of anhydrous ethanol, ammonia water, silicon dioxide particles, tetrabutylammonium bromide ethanol solution and tetraethyl orthosilicate is (45-50) mL: (1.5-2.5) mL: (0.08-0.1) g: (1-2) mL: (0.8-1.2) mL, the concentration of tetrabutylammonium bromide ethanol solution is 0.4 mol / L, the reaction time is 5-7 h, the centrifugal speed is 10000-12000 rpm, and the centrifugal time is 8-12 min.

[0010] Preferably, in Q2, the dosage ratio of decamethylcyclopentasiloxane, tetramethyltetravinylcyclotetrasiloxane, octaphenylcyclotetrasiloxane and tungsten oxide is (145-158) mL: (170-176) μL: (392-399) mg: (16-20) mg, the oil bath heating and stirring temperature is 90-110°C, the stirring reaction time is 80-100 min, dichloromethane is used for dissolution, and methanol is used for precipitation.

[0011] Preferably, in Q3, the usage ratio of the organic polymer, the inorganic particles, the dichloromethane and the photosensitive adhesive is (10-20) g: (0.3-0.5) g: (8-12) mL: (0.1-0.15) g, and the standing time is 8-12 h.

[0012] Preferably, the method for preparing the wear-resistant layer material comprises the following steps: S1: adding methyl methacrylate, butyl methacrylate, crotonic acid, hydroxyethyl methacrylate, octamethylcyclotetrasiloxane, xylene and azobisisobutyronitrile into a container, heating and stirring to react, and cooling after the reaction is completed to obtain a composite resin; S2: The composite resin is mixed with deionized water, and magnetically stirred at room temperature. Then, polytetrafluoroethylene emulsion is added, and magnetic stirring is continued to obtain a wear-resistant layer material.

[0013] In the above process, methyl methacrylate, butyl methacrylate, crotonic acid, hydroxyethyl methacrylate and octamethylcyclotetrasiloxane undergo free radical polymerization reaction under heating conditions to prepare a composite resin, and then the composite resin is mixed and stirred with a polytetrafluoroethylene emulsion to obtain a wear-resistant layer material.

[0014] Preferably, in S1, the amount ratio of methyl methacrylate, butyl methacrylate, crotonic acid, hydroxyethyl methacrylate, octamethylcyclotetrasiloxane, xylene and azobisisobutyronitrile is (11-15) g: (8-11) g: (0.3-0.5) g: (0.5-0.9) g: (1-3) g: (10-13) g: (0.32-0.38) g, the heating and stirring reaction temperature is 95-105°C, and the reaction time is 40-120 min.

[0015] Preferably, in S2, the dosage ratio of the composite resin, deionized water and polytetrafluoroethylene emulsion is (8-12) g: (7-9) mL: (0.2-0.5) mL, the mass fraction of the polytetrafluoroethylene emulsion is 60 wt%, the average particle size is 0.25 μm, the magnetic stirring speed is 500-800 rpm, the magnetic stirring time is 6-8 h, the continued magnetic speed is 600-800 rpm, and the stirring time is 3-5 h.

[0016] Preferably, the method for preparing a directional diffusion film comprises the following steps: Step 1: uniformly coating the prepared scattering layer material on one side of the polyethylene terephthalate, heating and UV curing to obtain a semi-pre-finished product; Step 2: Evenly spray the wear-resistant layer material on the other side of the polyethylene terephthalate, and after drying, obtain a directional diffusion film.

[0017] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: The invention uses tetraethyl orthosilicate, tetrabutylammonium bromide ethanol solution, decamethylcyclopentasiloxane, tetramethyltetravinylcyclotetrasiloxane and octaphenylcyclotetrasiloxane as raw materials to prepare a scattering layer material, and then uses methyl methacrylate, butyl methacrylate, crotonic acid, hydroxyethyl methacrylate, octamethylcyclotetrasiloxane and polytetrafluoroethylene emulsion as raw materials to prepare a wear-resistant layer material. The wear-resistant layer material is applied to the preparation process of a directional diffusion film, and the light diffusion performance, corrosion resistance and wear resistance of the diffusion film can be effectively improved.

[0018] 2. The present invention applies the prepared scattering layer material to the diffusion film, which can effectively improve the light diffusion performance of the diffusion film. The roughness of the surface of the inorganic particles increases the specific surface area, improves the interaction ability with the surrounding environment, and increases the irregular reflection and refraction points of the light on the particle surface, thereby achieving effective diffusion of light. At the same time, the higher the roughness of the particle surface, the higher the absolute value of its Zeta potential, which enhances the stability of the particle system, prevents particle agglomeration, and maintains the optical properties of the scattering layer material; the organic polymer has a flexible siloxane chain and good optical transparency, and its refractive index is different from that of the inorganic particles, which further enhances the scattering effect of the light at the interface between the inorganic particles and the polymer. The organic-inorganic hybrid light scattering particles combine the rigidity of the inorganic particles and the flexibility of the organic polymer to form a scattering center with structural diversity and complexity, so that the light encounters more scattering points of different shapes and sizes in the material. At the same time, the high stability and optical properties of the inorganic particles complement the flexibility and processing properties of the organic polymer, and jointly improve the light diffusion performance of the scattering layer material. When light enters the scattering layer material, it will be reflected and refracted multiple times at the interface between the inorganic particles and the organic polymer, and finally the light will be effectively diffused in all directions, thereby improving the light diffusion performance of the diffusion film.

[0019] 3. The present invention applies the prepared wear-resistant layer material to the diffusion membrane, which can effectively improve the corrosion resistance and wear resistance of the diffusion membrane. The composite resin is generated by free radical polymerization of monomers such as methyl methacrylate, has a long molecular chain and a moderate degree of crosslinking, and gives it high strength and toughness. The addition of octamethylcyclotetrasiloxane introduces a flexible siloxane segment, promotes the uniform distribution of polymer molecules, reduces stress concentration, and enhances wear resistance. After the polytetrafluoroethylene emulsion is mixed with the composite resin, the polytetrafluoroethylene particles are evenly dispersed in the resin matrix to form lubricating and wear-resistant micro-points, effectively reducing friction resistance and wear rate. The two are combined to form a dense wear-resistant layer, which has both high hardness and toughness, significantly improving the wear resistance of the material, and the high chemical stability of the polymer chain-based siloxane bond formed by the monomer, coupled with the extremely high chemical inertness of polytetrafluoroethylene, jointly resists the erosion of various chemical substances, and the synergistic effect of the two further enhances the corrosion resistance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 A schematic structural diagram of a directional diffusion film prepared by the present invention.

[0022] Description of the drawings: 1. substrate, 2. scattering layer, 3. wear-resistant layer. DETAILED DESCRIPTION

[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1: See Figure 1 As shown, a directional diffusion film comprises a substrate 1, a scattering layer 2 is arranged on one side of the substrate, and a wear-resistant layer 3 is arranged on the other side of the substrate.

[0025] Embodiment 2: This embodiment discloses a method for preparing a scattering layer material, comprising the following steps: Q1: 100 mL of anhydrous ethanol, 2.5 mL of distilled water and 8 mL of ammonia water were added to a container, stirred and mixed at 35°C and 400 rpm for 15 min, and then 2.5 mL of tetraethyl orthosilicate was added to react for 8 h. After the reaction, the mixture was centrifuged at 10,000 rpm for 12 min, and washed with distilled water and ethanol to obtain silica particles; 47.5 mL of anhydrous ethanol and 2 mL of ammonia water were added to a container, magnetically stirred, and then 0.09 g of silica particles and 1.5 mL of 0.4 mol / L tetrabutylammonium bromide ethanol solution were added, followed by 1 mL of tetraethyl orthosilicate. The mixture was reacted for 6 h, centrifuged at 12,000 rpm for 10 min, and purified to obtain inorganic particles; Q2: 151 mL of decamethylcyclopentasiloxane, 173 μL of tetramethyltetravinylcyclotetrasiloxane and 395 mg of octaphenylcyclotetrasiloxane were added to a container, heated in an oil bath at 100°C with stirring for 90 min, and then 18 mg of tungsten oxide and 5.2 μL of benzyl alcohol were added to the container, stirred for reaction, and after the reaction was completed, glacial acetic acid was added, dissolved with dichloromethane, and precipitated with methanol to obtain an organic polymer; Q3: Add the obtained 15g organic polymer and 0.4g inorganic particles into a container, add 10mL dichloromethane and stir, then add 0.13g photosensitive adhesive, stir evenly, and let stand for 10h to obtain a scattering layer material.

[0026] This embodiment discloses a method for preparing a wear-resistant layer material, comprising the following steps: S1: 13 g of methyl methacrylate, 9 g of butyl methacrylate, 0.4 g of crotonic acid, 0.7 g of hydroxyethyl methacrylate, 2 g of octamethylcyclotetrasiloxane, 11.5 g of xylene and 0.35 g of azobisisobutyronitrile were added to a container, heated and stirred at 100° C. for 110 min, and after the reaction was completed, cooled to obtain a composite resin; S2: 10 g of the composite resin was mixed with 8 mL of deionized water, and magnetically stirred at 600 rpm for 6 h at room temperature. Then, 0.35 mL of a polytetrafluoroethylene emulsion with a mass fraction of 60 wt % and an average particle size of 0.25 μm was added, and magnetic stirring was continued at 800 rpm for 4 h to obtain a wear-resistant layer material.

[0027] This embodiment discloses a method for preparing a directional diffusion film, comprising the following steps: Step 1: uniformly coating the prepared scattering layer material on one side of the polyethylene terephthalate, heating and UV curing to obtain a semi-pre-finished product; Step 2: Evenly spray the wear-resistant layer material on the other side of the polyethylene terephthalate, and after drying, obtain a directional diffusion film.

[0028] Embodiment 3: This embodiment discloses a method for preparing a scattering layer material, comprising the following steps: Q1: 80 mL of anhydrous ethanol, 2 mL of distilled water and 10 mL of ammonia water were added to a container, stirred and mixed at 35°C and 400 rpm for 15 min, and then 3 mL of tetraethyl orthosilicate was added to react for 8 h. After the reaction, centrifuged at 10,000 rpm for 12 min, and washed with distilled water and ethanol to obtain silica particles; 45 mL of anhydrous ethanol and 1.5 mL of ammonia water were added to a container, magnetically stirred, and then 0.08 g of silica particles and 1 mL of 0.4 mol / L tetrabutylammonium bromide ethanol solution were added, followed by 0.8 mL of tetraethyl orthosilicate, reacted for 6 h, centrifuged at 12,000 rpm for 10 min, and purified to obtain inorganic particles; Q2: 145 mL of decamethylcyclopentasiloxane, 170 μL of tetramethyltetravinylcyclotetrasiloxane and 392 mg of octaphenylcyclotetrasiloxane were added to a container, heated in an oil bath at 100°C with stirring for 90 min, and then 16 mg of tungsten oxide and 5.2 μL of benzyl alcohol were added to the container, stirred for reaction, and after the reaction was completed, glacial acetic acid was added, dissolved with dichloromethane, and precipitated with methanol to obtain an organic polymer; Q3: Add the obtained 10g organic polymer and 0.3g inorganic particles into a container, add 8mL dichloromethane and stir, then add 0.1g photosensitive adhesive, stir evenly, and let stand for 10h to obtain a scattering layer material.

[0029] This embodiment discloses a method for preparing a wear-resistant layer material, comprising the following steps: S1: 11 g of methyl methacrylate, 10 g of butyl methacrylate, 0.3 g of crotonic acid, 0.5 g of hydroxyethyl methacrylate, 1 g of octamethylcyclotetrasiloxane, 10 g of xylene and 0.32 g of azobisisobutyronitrile were added to a container, heated and stirred at 100° C. for 110 min, and after the reaction was completed, cooled to obtain a composite resin; S2: 12 g of the composite resin was mixed with 7 mL of deionized water, and magnetically stirred at 600 rpm for 6 h at room temperature. Then, 0.2 mL of a polytetrafluoroethylene emulsion with a mass fraction of 60 wt % and an average particle size of 0.25 μm was added, and magnetic stirring was continued at 800 rpm for 4 h to obtain a wear-resistant layer material.

[0030] This embodiment discloses a method for preparing a directional diffusion film, comprising the following steps: Step 1: uniformly coating the prepared scattering layer material on one side of the polyethylene terephthalate, heating and UV curing to obtain a semi-pre-finished product; Step 2: Evenly spray the wear-resistant layer material on the other side of the polyethylene terephthalate, and after drying, obtain a directional diffusion film.

[0031] Embodiment 4: This embodiment discloses a method for preparing a scattering layer material, comprising the following steps: Q1: 120 mL of anhydrous ethanol, 3 mL of distilled water and 6 mL of ammonia water were added to a container, stirred and mixed at 35°C and 400 rpm for 15 min, and then 2 mL of tetraethyl orthosilicate was added to react for 8 h. After the reaction, centrifuged at 10,000 rpm for 12 min, and washed with distilled water and ethanol to obtain silica particles; 50 mL of anhydrous ethanol and 2.5 mL of ammonia water were added to a container, magnetically stirred, and then 0.1 g of silica particles and 2 mL of 0.4 mol / L tetrabutylammonium bromide ethanol solution were added, followed by 1.2 mL of tetraethyl orthosilicate, reacted for 6 h, centrifuged at 12,000 rpm for 10 min, and purified to obtain inorganic particles; Q2: 158 mL of decamethylcyclopentasiloxane, 176 μL of tetramethyltetravinylcyclotetrasiloxane and 399 mg of octaphenylcyclotetrasiloxane were added to a container, heated in an oil bath at 100°C with stirring for 90 min, and then 20 mg of tungsten oxide and 5.2 μL of benzyl alcohol were added to the container, stirred for reaction, and after the reaction was completed, glacial acetic acid was added, dissolved with dichloromethane, and precipitated with methanol to obtain an organic polymer; Q3: Add the obtained 20g organic polymer and 0.5g inorganic particles into a container, add 12mL dichloromethane and stir, then add 0.15g photosensitive adhesive, stir evenly, and let stand for 10h to obtain a scattering layer material.

[0032] This embodiment discloses a method for preparing a wear-resistant layer material, comprising the following steps: S1: 15 g of methyl methacrylate, 11 g of butyl methacrylate, 0.5 g of crotonic acid, 0.9 g of hydroxyethyl methacrylate, 3 g of octamethylcyclotetrasiloxane, 13 g of xylene and 0.38 g of azobisisobutyronitrile were added to a container, heated and stirred at 100° C. for 110 min, and after the reaction was completed, cooled to obtain a composite resin; S2: 8 g of the composite resin was mixed with 9 mL of deionized water, and magnetically stirred at 600 rpm for 6 h at room temperature. Then, 0.5 mL of a polytetrafluoroethylene emulsion with a mass fraction of 60 wt % and an average particle size of 0.25 μm was added, and magnetic stirring was continued at 800 rpm for 4 h to obtain a wear-resistant layer material.

[0033] This embodiment discloses a method for preparing a directional diffusion film, comprising the following steps: Step 1: uniformly coating the prepared scattering layer material on one side of the polyethylene terephthalate, heating and UV curing to obtain a semi-pre-finished product; Step 2: Evenly spray the wear-resistant layer material on the other side of the polyethylene terephthalate, and after drying, obtain a directional diffusion film.

[0034] Embodiment 5: This embodiment discloses a method for preparing a scattering layer material, comprising the following steps: Q1: 110 mL of anhydrous ethanol, 2.1 mL of distilled water and 7 mL of ammonia water were added to a container, stirred and mixed at 35°C and 400 rpm for 15 min, and then 2.2 mL of tetraethyl orthosilicate was added to react for 8 h. After the reaction, centrifuged at 10,000 rpm for 12 min, and washed with distilled water and ethanol to obtain silica particles; 46 mL of anhydrous ethanol and 1.8 mL of ammonia water were added to a container, magnetically stirred, and then 0.09 g of silica particles and 1.1 mL of 0.4 mol / L tetrabutylammonium bromide ethanol solution were added, followed by 0.9 mL of tetraethyl orthosilicate, reacted for 6 h, centrifuged at 12,000 rpm for 10 min, and purified to obtain inorganic particles; Q2: 146 mL of decamethylcyclopentasiloxane, 171 μL of tetramethyltetravinylcyclotetrasiloxane and 393 mg of octaphenylcyclotetrasiloxane were added to a container, heated in an oil bath at 100°C with stirring for 90 min, and then 17 mg of tungsten oxide and 5.2 μL of benzyl alcohol were added to the container, stirred for reaction, and after the reaction was completed, glacial acetic acid was added, dissolved with dichloromethane, and precipitated with methanol to obtain an organic polymer; Q3: Add 12 g of the obtained organic polymer and 0.35 g of inorganic particles into a container, add 9 mL of dichloromethane and stir, then add 0.12 g of photosensitive adhesive, stir evenly, and let stand for 10 hours to obtain a scattering layer material.

[0035] This embodiment discloses a method for preparing a wear-resistant layer material, comprising the following steps: S1: 12 g of methyl methacrylate, 8 g of butyl methacrylate, 0.35 g of crotonic acid, 0.6 g of hydroxyethyl methacrylate, 1.5 g of octamethylcyclotetrasiloxane, 11 g of xylene and 0.34 g of azobisisobutyronitrile were added to a container, heated and stirred at 100° C. for 110 min, and after the reaction was completed, cooled to obtain a composite resin; S2: 9 g of the composite resin was mixed with 7.5 mL of deionized water, and magnetically stirred at 600 rpm for 6 h at room temperature. Then, 0.3 mL of a polytetrafluoroethylene emulsion with a mass fraction of 60 wt % and an average particle size of 0.25 μm was added, and magnetic stirring was continued at 800 rpm for 4 h to obtain a wear-resistant layer material.

[0036] This embodiment discloses a method for preparing a directional diffusion film, comprising the following steps: Step 1: uniformly coating the prepared scattering layer material on one side of the polyethylene terephthalate, heating and UV curing to obtain a semi-pre-finished product; Step 2: Evenly spray the wear-resistant layer material on the other side of the polyethylene terephthalate, and after drying, obtain a directional diffusion film.

[0037] Embodiment 6: This embodiment discloses a method for preparing a scattering layer material, comprising the following steps: Q1: 90 mL of anhydrous ethanol, 2.8 mL of distilled water and 9 mL of ammonia water were added to a container, stirred and mixed at 35°C and 400 rpm for 15 min, and then 2.7 mL of tetraethyl orthosilicate was added to react for 8 h. After the reaction, centrifuged at 10,000 rpm for 12 min, and washed with distilled water and ethanol to obtain silica particles; 48 mL of anhydrous ethanol and 2.2 mL of ammonia water were added to a container, magnetically stirred, and then 0.08 g of silica particles and 1.7 mL of 0.4 mol / L tetrabutylammonium bromide ethanol solution were added, followed by 1.1 mL of tetraethyl orthosilicate, reacted for 6 h, centrifuged at 12,000 rpm for 10 min, and purified to obtain inorganic particles; Q2: 152 mL of decamethylcyclopentasiloxane, 175 μL of tetramethyltetravinylcyclotetrasiloxane and 396 mg of octaphenylcyclotetrasiloxane were added to a container, heated in an oil bath at 100°C with stirring for 90 min, and then 19 mg of tungsten oxide and 5.2 μL of benzyl alcohol were added to the container, stirred for reaction, and after the reaction was completed, glacial acetic acid was added, dissolved with dichloromethane, and precipitated with methanol to obtain an organic polymer; Q3: Add the obtained 18g organic polymer and 0.45g inorganic particles into a container, add 11mL dichloromethane and stir, then add 0.14g photosensitive adhesive, stir evenly, and let stand for 10 hours to obtain a scattering layer material.

[0038] This embodiment discloses a method for preparing a wear-resistant layer material, comprising the following steps: S1: 14 g of methyl methacrylate, 8.5 g of butyl methacrylate, 0.45 g of crotonic acid, 0.8 g of hydroxyethyl methacrylate, 2.5 g of octamethylcyclotetrasiloxane, 12 g of xylene and 0.36 g of azobisisobutyronitrile were added to a container, heated and stirred at 100° C. for 110 min, and after the reaction was completed, cooled to obtain a composite resin; S2: 10 g of the composite resin was mixed with 8.5 mL of deionized water, and magnetically stirred at 600 rpm for 6 h at room temperature. Then, 0.4 mL of a polytetrafluoroethylene emulsion with a mass fraction of 60 wt % and an average particle size of 0.25 μm was added, and magnetic stirring was continued at 800 rpm for 4 h to obtain a wear-resistant layer material.

[0039] This embodiment discloses a method for preparing a directional diffusion film, comprising the following steps: Step 1: uniformly coating the prepared scattering layer material on one side of the polyethylene terephthalate, heating and UV curing to obtain a semi-pre-finished product; Step 2: Evenly spray the wear-resistant layer material on the other side of the polyethylene terephthalate, and after drying, obtain a directional diffusion film.

[0040] Embodiment 7: This embodiment discloses a method for preparing a scattering layer material, comprising the following steps: Q1: 105 mL of anhydrous ethanol, 2.4 mL of distilled water and 6.5 mL of ammonia water were added to a container, stirred and mixed at 35°C and 400 rpm for 15 min, and then 2.6 mL of tetraethyl orthosilicate was added to react for 8 h. After the reaction, centrifuged at 10,000 rpm for 12 min, and washed with distilled water and ethanol to obtain silica particles; 49 mL of anhydrous ethanol and 2.1 mL of ammonia water were added to a container, magnetically stirred, and then 0.1 g of silica particles and 1.4 mL of 0.4 mol / L tetrabutylammonium bromide ethanol solution were added, followed by 0.85 mL of tetraethyl orthosilicate, reacted for 6 h, centrifuged at 12,000 rpm for 10 min, and purified to obtain inorganic particles; Q2: 155 mL of decamethylcyclopentasiloxane, 174 μL of tetramethyltetravinylcyclotetrasiloxane and 394 mg of octaphenylcyclotetrasiloxane were added to a container, heated in an oil bath at 100°C with stirring for 90 min, and then 16 mg of tungsten oxide and 5.2 μL of benzyl alcohol were added to the container, stirred for reaction, and after the reaction was completed, glacial acetic acid was added, dissolved with dichloromethane, and precipitated with methanol to obtain an organic polymer; Q3: Add 19 g of the obtained organic polymer and 0.38 g of inorganic particles into a container, add 10.5 mL of dichloromethane and stir, then add 0.14 g of photosensitive adhesive, stir evenly, and let stand for 10 hours to obtain a scattering layer material.

[0041] This embodiment discloses a method for preparing a wear-resistant layer material, comprising the following steps: S1: 12.5 g of methyl methacrylate, 9.5 g of butyl methacrylate, 0.38 g of crotonic acid, 0.55 g of hydroxyethyl methacrylate, 2.2 g of octamethylcyclotetrasiloxane, 10.5 g of xylene and 0.37 g of azobisisobutyronitrile were added to a container, heated and stirred at 100° C. for 110 min, and after the reaction was completed, cooled to obtain a composite resin; S2: 8.5 g of the composite resin was mixed with 8.8 mL of deionized water, and magnetically stirred at 600 rpm for 6 h at room temperature. Then, 0.25 mL of a polytetrafluoroethylene emulsion with a mass fraction of 60 wt % and an average particle size of 0.25 μm was added, and magnetic stirring was continued at 800 rpm for 4 h to obtain a wear-resistant layer material.

[0042] This embodiment discloses a method for preparing a directional diffusion film, comprising the following steps: Step 1: uniformly coating the prepared scattering layer material on one side of the polyethylene terephthalate, heating and UV curing to obtain a semi-pre-finished product; Step 2: Evenly spray the wear-resistant layer material on the other side of the polyethylene terephthalate, and after drying, obtain a directional diffusion film.

[0043] Comparative Example 1: Compared with Example 2, in Comparative Example 1, no scattering layer material is added during the preparation of the directional diffusion film, and other conditions remain unchanged.

[0044] Comparative Example 2: Compared with Example 2, in Comparative Example 2, the wear-resistant layer material is not sprayed during the preparation of the directional diffusion membrane, and other conditions remain unchanged.

[0045] Experimental example: The samples prepared in Examples 2-7 and Comparative Examples 1-2 were subjected to performance tests, and the diffusion angle of the samples was tested. The test method was as follows: a beam of red laser was used to pass through the sample, and a white screen was used to receive the laser passing through. A circular spot of light appeared on the receiving screen. The distance between the laser and the sample was fixed at 0.1m, the distance L between the sample and the receiving screen was 1m, the spot radius was R, and the value of R was measured. The diffusion angle θ=2arctan(R / L). The larger the diffusion angle, the better the diffusion effect. The wear resistance of the samples was tested in accordance with GB / T9867-2008, and the corrosion resistance of the samples was tested in accordance with GB / T2423.17-2024. The test results are shown in Table 1: Table 1 project Diffusion angle / ° Wear index / % Quality loss rate / % Example 2 17.23 3.46 2.44 Example 3 17.11 3.52 2.76 Example 4 16.96 3.48 2.87 Example 5 16.84 3.58 3.12 Example 6 16.79 3.53 3.58 Example 7 16.77 3.63 3.36 Comparative Example 1 13.34 3.68 3.43 Comparative Example 2 16.75 7.12 5.84 From the test results in Table 1, it can be seen that the diffusion films prepared in Examples 2-7 of the present invention have excellent light diffusion performance, corrosion resistance and wear resistance. From the comparison between Comparative Example 1 and Examples 2-7, it can be seen that adding a scattering layer material can effectively improve the light diffusion performance of the diffusion film; from the comparison between Comparative Example 2 and Examples 2-7, it can be seen that adding a wear-resistant layer material can effectively improve the corrosion resistance and wear resistance of the diffusion film.

[0046] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0047] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A directional diffusion film, characterized in that: The directional diffusion film comprises a substrate, a scattering layer is arranged on one side of the substrate, and a wear-resistant layer is arranged on the other side; the substrate layer is made of polyethylene terephthalate as a raw material, the scattering layer material is prepared from tetraethyl orthosilicate, tetrabutylammonium bromide ethanol solution, decamethylcyclopentasiloxane, tetramethyltetravinylcyclotetrasiloxane and octaphenylcyclotetrasiloxane, and the wear-resistant layer material is prepared from methyl methacrylate, butyl methacrylate, crotonic acid, hydroxyethyl methacrylate, octamethylcyclotetrasiloxane and polytetrafluoroethylene emulsion.

2. A directional diffusion film according to claim 1, characterized in that: The method for preparing the scattering layer material comprises the following steps: Q1: Add anhydrous ethanol, distilled water and ammonia water into a container, stir and mix, then add tetraethyl orthosilicate to react, centrifuge and wash after the reaction to obtain silica particles; add anhydrous ethanol and ammonia water into a container, stir magnetically, add silica particles and tetrabutylammonium bromide ethanol solution, then add tetraethyl orthosilicate, react, centrifuge and purify to obtain inorganic particles; Q2: Add decamethylcyclopentasiloxane, tetramethyltetravinylcyclotetrasiloxane and octaphenylcyclotetrasiloxane into a container, heat and stir in an oil bath, then add tungsten oxide and benzyl alcohol into the container, stir and react, after the reaction is completed, add glacial acetic acid, dissolve, precipitate, and obtain an organic polymer; Q3: Add the obtained organic polymer and inorganic particles into a container, add dichloromethane and stir, then add photosensitive adhesive, stir evenly, and let stand to obtain a scattering layer material.

3. A directional diffusion film according to claim 2, characterized in that: In the Q1, the dosage ratio of anhydrous ethanol, distilled water, ammonia water and tetraethyl orthosilicate is (80-120) mL: (2-3) mL: (6-10) mL: (2-3) mL, the stirring mixing temperature is 30-35°C, the stirring speed is 300-400 rpm, the time is 10-15 min, the reaction time is 6-8 h, the centrifugal speed is 10000-12000 rpm, the time is 10-12 min, and the distilled water and ethanol are used for washing. The dosage ratio of anhydrous ethanol, ammonia water, silica particles, tetrabutylammonium bromide ethanol solution and tetraethyl orthosilicate is (45-50) mL: (1.5-2.5) mL: (0.08-0.1) g: (1-2) mL: (0.8-1.2) mL, the concentration of tetrabutylammonium bromide ethanol solution is 0.4 mol / L, the reaction time is 5-7 h, the centrifugal speed is 10000-12000 rpm, and the centrifugal time is 8-12 min.

4. A directional diffusion film according to claim 2, characterized in that: In the Q2, the dosage ratio of decamethylcyclopentasiloxane, tetramethyltetravinylcyclotetrasiloxane, octaphenylcyclotetrasiloxane and tungsten oxide is (145-158) mL: (170-176) μL: (392-399) mg: (16-20) mg, the oil bath heating and stirring temperature is 90-110° C., the stirring reaction time is 80-100 min, dichloromethane is used for dissolution, and methanol is used for precipitation.

5. The directional diffusion film according to claim 2, characterized in that: In Q3, the usage ratio of the organic polymer, the inorganic particles, the dichloromethane and the photosensitive adhesive is (10-20) g: (0.3-0.5) g: (8-12) mL: (0.1-0.15) g, and the standing time is 8-12 h.

6. The directional diffusion film according to claim 1, characterized in that: The preparation method of the wear-resistant layer material comprises the following steps: S1: adding methyl methacrylate, butyl methacrylate, crotonic acid, hydroxyethyl methacrylate, octamethylcyclotetrasiloxane, xylene and azobisisobutyronitrile into a container, heating and stirring to react, and cooling after the reaction is completed to obtain a composite resin; S2: The composite resin is mixed with deionized water, and magnetically stirred at room temperature. Then, polytetrafluoroethylene emulsion is added, and magnetic stirring is continued to obtain a wear-resistant layer material.

7. A directional diffusion film according to claim 6, characterized in that: In the S1, the amount ratio of methyl methacrylate, butyl methacrylate, crotonic acid, hydroxyethyl methacrylate, octamethylcyclotetrasiloxane, xylene and azobisisobutyronitrile is (11-15) g: (8-11) g: (0.3-0.5) g: (0.5-0.9) g: (1-3) g: (10-13) g: (0.32-0.38) g, the heating and stirring reaction temperature is 95-105° C., and the reaction time is 40-120 min.

8. The directional diffusion film according to claim 6, characterized in that: In S2, the dosage ratio of the composite resin, deionized water and polytetrafluoroethylene emulsion is (8-12) g: (7-9) mL: (0.2-0.5) mL, the mass fraction of the polytetrafluoroethylene emulsion is 60 wt%, the average particle size is 0.25 μm, the magnetic stirring speed is 500-800 rpm, the magnetic stirring time is 6-8 h, the continued magnetic speed is 600-800 rpm, and the stirring time is 3-5 h.

9. A method for preparing a directional diffusion film according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1: uniformly coating the prepared scattering layer material on one side of the polyethylene terephthalate, heating and UV curing to obtain a semi-finished product; Step 2: Evenly spray the wear-resistant layer material on the other side of the polyethylene terephthalate, and after drying, obtain a directional diffusion film.